Micro‐Electromechanical Switch: A 0.2 V Micro‐Electromechanical Switch Enabled by a Phase Transition (Small 14/2018). Issue 14 (6th April 2018) - Dong, Kaichen; Choe, Hwan Sung; Wang, Xi; Liu, Huili; Saha, Bivas; Ko, Changhyun; Deng, Yang; Tom, Kyle B.; Lou, Shuai; Wang, Letian; Grigoropoulos, Costas P.; You, Zheng; et al.
Abstract : In article number1703621, Zheng You, Jie Yao, Junqiao Wu, and co‐workers demonstrate a micro‐electromechanical (MEM) switch with 0.2 V operating voltage and ≳10 6 safe operating cycles in ambient air, which is mainly enabled by the abrupt phase transition of nanolayered vanadium dioxide slightly above room temperature. This device is also used to demonstrate a temperature alarm/switch with ultralow power consumption. Such phase‐transition MEM switches would open possibilities for sub 1 V hybrid integrated devices/circuits/systems and ultralow power consumption devices for practical applications.